2011
DOI: 10.1088/2041-8205/729/2/l24
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Driven Atmospheric Escape: Transition From Hydrodynamic to Jeans Escape

Abstract: Thermally-driven atmospheric escape evolves from an organized outflow (hydrodynamic escape) to escape on a molecule by molecules basis (Jeans escape) with increasing Jeans parameter, the ratio of the gravitational to thermal energy of molecules in a planet's atmosphere.This transition is described here using the direct simulation Monte Carlo method for a single component spherically symmetric atmosphere. When the heating is predominantly below the lower boundary of the simulation region, R 0 , and well below t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 31 publications
7
108
0
Order By: Relevance
“…It is also worth to mention that our results agree with the kinetic simulations of Volkov et al (2011) whose simulations yield a very sharp growth of the escape rate, when the β parameter decreases from 2.7 to 2. For β values 2 this kinetic simulations predict only supersonic flow.…”
Section: Analytical and Numerical Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It is also worth to mention that our results agree with the kinetic simulations of Volkov et al (2011) whose simulations yield a very sharp growth of the escape rate, when the β parameter decreases from 2.7 to 2. For β values 2 this kinetic simulations predict only supersonic flow.…”
Section: Analytical and Numerical Resultssupporting
confidence: 88%
“…Generally, the main necessary condition for hydrodynamic escape modeling is that the sonic point c 2014 RAS should be within the collision dominated atmosphere where the Knudsen number Kn is sufficiently small. Volkov et al (2011) suggested a criterion where hydrodynamic models should be valid without problems as long as the Kn 0.1. In our present study we investigate the escape criteria and efficiency of atomic hydrogen from a Mars-like planetary embryo at 1 AU that experiences XUV flux values between 45-100 times higher than that of today's solar value.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the case of the well-studied hydrogen-rich hot gas giant HD 209458b with a skin temperature T 0 * 1350 K and a XUV flux *453 times higher compared to that of today's solar value, Eq. 29 leads to a thermal mass loss rate in the order of a few *10 10 g s -1 (e.g., Erkaev et al, 2007;Lammer et al, 2009), which is comparable to models solving similar hydrodynamic equations of mass, momentum, and energy conservation as in the present study (e.g., Yelle, 2004;Tian et al, 2005a;García Muñ oz, 2007;Penz et al, 2008;Volkov et al, 2011;Koskinen et al, 2013).…”
Section: Erkaev Et Alsupporting
confidence: 75%
“…These observations indicate that close-in EGPs such as HD209458b are surrounded by a hot thermosphere composed of atomic hydrogen that extends to several planetary radii and provide the required line of [20,21] and their application to close-in EGPs [8,9]. We then proceed to generalize the results to a sample of known EGPs to make specific predictions about the nature of their upper atmospheres.…”
Section: Introductionmentioning
confidence: 91%